AN EMPIRICAL STUDY ON EXPLORING EMPLOYERS’ OUTLOOK TOWARDS DYNAMICS OF EMPLOYEE ENGAGEMENT IN THE DOMESTIC HELP SECTOR WITH SPECIAL REFERENCE TO NAVI MUMBAI - Maumita Roy; Bhute, Anjali (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Domestic workers constitute a vital part of the informal labor sector globally and in India, where their presence has significantly increased, especially after economic liberalization. Predominantly female, this workforce plays a critical role in supporting households, especially in urban centers where dual-income families are common. Despite their importance, domestic workers often operate in unregulated environments marked by poor working conditions, job insecurity, and a lack of formal recognition. This study investigates the employer-employee dynamics in the domestic help sector, with a specific focus on employer perceptions in Navi Mumbai. Through a structured survey method and statistical analysis including logistic regression and non-parametric tests, the research explores how demographic factors such as age, gender, and profession influence employer behavior and attitudes toward domestic workers. The findings offer a balanced understanding of both employer and employee perspectives, aiming to contribute toward a more structured and equitable model for domestic employment.